Hunters of the Past: A Study of Demography, Attitudes, and Values among Danish Metal Detector Users - Lykkegård-Maes, Mette; Dobat, Andres Siegfried (Danish Journal of Archaeology, 2022)
This article presents the results of a questionnaire-based survey on demographic aspects and prevailing attitudes, motivations and values among the Danish hobbyist metal detector community. The objective is to take a first step towards a scholarly appraisal of the social dimension of the metal detector phenomenon - e.g. its people as members of a community with its own specific and probably often diverging characteristics and dynamics. Hereby we want to contribute to shaping a best practice framework for interacting and cooperating with detectorists in Denmark and internationally.